2021
DOI: 10.1016/j.foodcont.2020.107500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food safety training on behavior change of food handlers: A case of orange-fleshed sweetpotato purée processing in Kenya

Abstract: Sweetpotato purée processing is new to Kenya and a rapidly growing value addition activity among informal, small, and medium-sized food enterprises (SMEs) in sub-Saharan Africa (SSA). Inadequate knowledge of food safety and poor hygiene practices by food handlers, low level of compliance with Good Manufacturing Practices (GMPs), and microbial contamination are major food safety challenges in orange-fleshed sweetpotato (OFSP) purée processing in Kenya. The extent of food safety training in enhancing food safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
26
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 33 publications
10
26
2
2
Order By: Relevance
“…Previous training on food safety increased the odds of complying with food hygiene measures. These ndings were consistent with another study conducted in Kenya (Malavi et al, 2021). A crucial part of ensuring adherence to food hygiene regulations is food safety training.…”
Section: Discussionsupporting
confidence: 91%
“…Previous training on food safety increased the odds of complying with food hygiene measures. These ndings were consistent with another study conducted in Kenya (Malavi et al, 2021). A crucial part of ensuring adherence to food hygiene regulations is food safety training.…”
Section: Discussionsupporting
confidence: 91%
“…Although washing hands is very easy to do, there are still many traders who underestimate it. This finding is in line with the results of research in Kenya that processed foods that are newly popular in the region need attention to hygiene sanitation because they are prone to coliform bacteria contamination (Malavi, Abong, & Muzhingi, 2021) The presence of Coliform in Thai Tea can also be influenced by the water (Sinaga et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…For example, a comparison between restaurants in which outbreaks had occurred and those without outbreaks, it has been shown that qualifications of kitchen managers, including food safety training, were critical in preventing the outbreaks [15,16]. The results of a study conducted in Kenya point to food safety training as an appropriate means of improving the knowledge and hygienic practices of food handlers [17]. Education of food handlers is a preventive measure that leads to the reduction of food safety risks.…”
Section: Introductionmentioning
confidence: 99%